2024
DOI: 10.3390/ijms25063086
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Management of Diabetic Kidney Disease: Slowing Progression

Na Wang,
Chun Zhang

Abstract: Diabetic kidney disease (DKD) is a major cause of chronic kidney disease (CKD), and it heightens the risk of cardiovascular incidents. The pathogenesis of DKD is thought to involve hemodynamic, inflammatory, and metabolic factors that converge on the fibrotic pathway. Genetic predisposition and unhealthy lifestyle practices both play a significant role in the development and progression of DKD. In spite of the recent emergence of angiotensin receptors blockers (ARBs)/angiotensin converting enzyme inhibitor (AC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 237 publications
(309 reference statements)
0
0
0
Order By: Relevance
“…The cellular signaling responses include growth factor signaling, the response to nitric oxide, the response to oxidative stress, the cytokine response, macrophage signaling, the TLR pathway, the T-cell-mediated response, NFκB factor activity, ERK/MAPK signaling, the JAK/STAT pathway, the WNT/β-catenin pathway, and NADPH oxidase activity. Several of these pathways are known to be implicated in GEC injury, inflammation, and fibrosis associated with DKD [6,8,11,17]. Similarly, the analyses suggested that the apoptotic processes, the response to cytokines, the T-cell-mediated response, the immune response, calcium channel activity, and growth factor signaling were the most frequent and active biological processes in DKD (Figures 6 and 7).…”
Section: Top-ranked Intersecting Cellular Functions and Signaling Pro...mentioning
confidence: 81%
See 1 more Smart Citation
“…The cellular signaling responses include growth factor signaling, the response to nitric oxide, the response to oxidative stress, the cytokine response, macrophage signaling, the TLR pathway, the T-cell-mediated response, NFκB factor activity, ERK/MAPK signaling, the JAK/STAT pathway, the WNT/β-catenin pathway, and NADPH oxidase activity. Several of these pathways are known to be implicated in GEC injury, inflammation, and fibrosis associated with DKD [6,8,11,17]. Similarly, the analyses suggested that the apoptotic processes, the response to cytokines, the T-cell-mediated response, the immune response, calcium channel activity, and growth factor signaling were the most frequent and active biological processes in DKD (Figures 6 and 7).…”
Section: Top-ranked Intersecting Cellular Functions and Signaling Pro...mentioning
confidence: 81%
“…Metabolic abnormalities activate the mononuclear phagocyte system, which releases pro-inflammatory cytokines and paracrine signals, leading to immune cell infiltration [6][7][8][9]. In the early stages of diabetes, glomerular and tubular cells have increased expression of tumor necrosis factor (TNF) α, interleukin (IL)-6, IL-1, and adhesion molecules [10,11]. Previous experimental studies showed that hyperglycemia promotes the imbalance in macrophage phenotypes and chronic glucose exacerbates the regulation of inflammatory responses [12,13].…”
Section: Introductionmentioning
confidence: 99%